Additional morphological characters and a new host for Aceria gymnoscuta Navia & Flechtmann (Acari, Eriophyidae) - [Anonymous] (Soc Brasileira Zoologia, Univ Federal Parana, 2005)
Aceria gymnoscuta Navia & Flechtmann, 2002 was originally described based on specimens collected on Syagrus cocoides Mart. and Syagrus flexuosa (Mart.) Becc. (Arecaceae). Slight variations in the dorsal shield pattern and the sternal line, in relation to the original description, and details on male and female genitalia are mentioned in this paper, based on specimens collected on a new host, Syagrus oleracea (Mart.) Becc..